A simple protocol for combinatorial cyclic depsipeptide libraries sequencing by matrix‐assisted laser desorption/ionisation mass spectrometry. (25th November 2014) - Gurevich‐Messina, Juan M.; Giudicessi, Silvana L.; Martínez‐Ceron, María C.; Acosta, Gerardo; Erra‐Balsells, Rosa; Cascone, Osvaldo; Albericio, Fernando; Camperi, Silvia A.
<x xml:space="preserve">Abstract</x> Short cyclic peptides have a great interest in therapeutic, diagnostic and affinity chromatography applications. The screening of 'one‐bead‐one‐peptide' combinatorial libraries combined with mass spectrometry (MS) is an excellent tool to find peptides with affinity for any target protein. The fragmentation patterns of cyclic peptides are quite more complex than those of their linear counterparts, and the elucidation of the resulting tandem mass spectra is rather more difficult. Here, we propose a simple protocol for combinatorial cyclic libraries synthesis and ring opening before MS analysis. In this strategy, 4‐hydroxymethylbenzoic acid, which forms a benzyl ester with the first amino acid, was used as the linker. A glycolamidic ester group was incorporated after the combinatorial positions by adding glycolic acid. The library synthesis protocol consisted in the following: (i) incorporation of Fmoc‐Asp[2‐phenylisopropyl (OPp)]‐OH to Ala‐Gly‐oxymethylbenzamide‐ChemMatrix, (ii) synthesis of the combinatorial library, (iii) assembly of a glycolic acid, (iv) couple of an Ala residue in the N‐terminal, (v) removal of OPp, (vi) peptide cyclisation through side chain Asp and N‐Ala amino terminus and (vii) removal of side chain protecting groups. In order to simultaneously open the ring and release each peptide, benzyl and glycolamidic esters were cleaved with ammonia. Peptide sequences could be deduced from the tandem mass spectra of each single bead evaluated. The strategy herein proposed is suitable for the preparation of one‐bead‐one‐cyclic depsipeptide libraries that can be easily open for its sequencing by matrix‐assisted laser desorption/ionisation MS. It employs techniques and reagents frequently used in a broad range of laboratories without special expertise in organic synthesis. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.